Rastreio da sarcopenia e fraqueza muscular respiratória em idosos hospitalizados em um Hospital Universitário do interior de São Paulo - uma contribuição para a intervenção da fisioterapia - Silva, Ana Caroline Simões (Universidade Federal de São Carlos, 2023)
With the increase in longevity in recent years, the association of comorbidities and clinical manifestations, such as frailty and sarcopenia, have acquired exponential importance, since with the aging process there is a gradual reduction in functional capacity, directly impacting quality of life of the elderly. In the context of hospitalizations, the loss of functionality and muscle strength is accentuated. In that In this sense, tracking the incidence of these conditions can provide support for specific intervention proposals for elderly people hospitalized with sarcopenia and muscle weakness, thus minimizing the losses caused by hospitalization in this population. Objectives: To evaluate the incidence of sarcopenia and respiratory muscle weakness in elderly people hospitalized at the University Hospital. Methods: Prospective, cross-sectional and observational study. Study prospective, transversal and observational. Hospitalized elderly people over the age of 60 were recruited. Functional performance was assessed by the 6-meter Gait Speed Test (MVT), respiratory muscle strength through manovacuometry using Maximum Inspiratory Pressure (MIP), in addition to peripheral muscle strength using Palm Grip Dynamometry (HPP). In addition to collecting clinical, nutritional, comorbidity and cognitive status data. Results: 28 elderly people with a mean age of 71 ± 9 years were evaluated, 18 of whom were men (64.28%). The risk of sarcopenia was present in 51.57% of the elderly people evaluated, while the confirmation and severity of sarcopenia was observed in 4 elderly people, 14.28% of the total sample. Functional performance was low in 92.85% of the elderly and the majority had reduced peripheral and respiratory muscle strength when compared to predicted values. Furthermore, nutritional status showed a statistically negative correlation with sarcopenia and a positive correlation with HGS. Conclusion: In screening, the risk of Sarcopenia was present in more than half of the elderly people evaluated and confirmed in 4 elderly people. Furthermore, most elderly people have low functional performance and compromised nutritional status. Nutritional status was positively associated with handgrip strength and negatively associated with the risk of sarcopenia
Screening for sarcopenia and respiratory muscle weakness in the elderly hospitalized in a University Hospital in the interior of São Paulo - a contribution to physiotherapy intervention
Keywords: Sarcopenia; Fraqueza muscular; Idosos; Fisioterapia; Hospitalização; Rastreio; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL